Retraction: Metabolism Determination By Soft Computing Methods From Breath Molecules - Ismail Bayraklı; Hatice Akman; Sedat Metlek (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The article whose title is given above was retracted by the decision of the Editorial Board upon the request of the authors.